DUAL SECTOR INFLATION DYNAMICS IN PAKISTAN: AN EMPIRICAL ANALYSIS USING COINTEGRATION ANALYSIS - Shaheen, Ruqia; Iqbal, Sidra; Javed, Aiman; Bintemaryam, (The journal of contemporary issues in business and government, 2021)
Dual sector inflation is essential for any country, and so it is for Pakistan. In this study, we estimate the long-run and short-run relationship among the variables using 1974 to 2020. The ARDL technique is used for this purpose. Data has been collected by the World Development Indicator and also by Hand Book of statistics. Data consists of time series data. When the price level of goods and services increases, people will chase few goods and commodities. This will have a significant impact on the economy. As a result, economic growth will significantly be affected to either move upward or maybe in a downward direction. There are many types of inflation which are demand-pull inflation, cost-push inflation, and built-in inflation. From an economics point of view, inflation is a regular increase or rise in the general price level of goods and services in an economy. When the general price level increases, every unit of paper money buys fewer goods and services. Inflation reflects a reduction in the consumer's purchasing power per unit of money currency, which is the loss of real value. Inflation is increasing day by day and is having the worst effect on the economy. It is controlled by Fiscal Policy as well as monetary policy.